Optimal allocation of distribution static compensators using a developed multi-objective sine cosine approach. (July 2020) - Selim, Ali; Kamel, Salah; Jurado, Francisco
Abstract: In this paper, the optimal allocation of Distribution STATic COMpensators (DSTATCOMs) in distribution networks is determined using an efficient optimization approach. In this approach, the Multi-Objective Sine Cosine Algorithm (MOSCA) is combined with Fuzzy Loss sensitivity Factor (FLSF) and grey relational analysis. FLSF is applied for determining the candidate buses which considered more suitable to be connected with the DSTATCOMs. Consequently, the search space of MOSCA will be reduced and its efficiency will be improved. A decision making based on grey relation analysis is applied for selecting the best solution among the available solutions for three objective functions. In this study, the DSTATCOMs are optimally allocated with the aim of reducing the total power losses, minimizing the Voltage Deviation (VD), as well as maximizing the Voltage Stability Index (VSI). To demonstrate the effectiveness of developed approach, the developed approach is comprehensively compared with well-known optimization algorithms to show its effectiveness in solving the studied problem. Different test systems (IEEE-33 bus, IEEE-69 bus, and 94 Portuguese distribution systems) are used for validation. However, the obtained results prove the effectiveness and superiority of developed approach compared with other optimization algorithms.